Basics of Landscape Design as a Designer Activity (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This article is devoted to the issues of landscape design. Using the acquired knowledge, skills and abilities of students of architectural universities in practice for their professional growth, the historical experience is considered, special attention is paid to the methodology of execution of project tasks, for their effective implementation. The arguments about increasing the landscape literacy of the masses are given, for the purpose of harmonious interaction of society and nature, preservation and competent use of earth resources and popularization of this profession as a whole.